(untitled) (Philippines, 1999)
Rice, unlike other cereals, has remarkable adaptability to a wide range of hydrological conditions. Although it can achieve its highest yield in waterlogged conditions under irrigation, it is widely grown in rainfed lowlands and uplands where soils are kept aerobic for a certain period or the entire period of crop growth. Aerobic exposure drastically changes the microenvironment for rice growth and increases environmental constraints that seriously affect crop production.
Keywords: Rice genetics,Cây lúa; Water environment